Fanzine Multisemiotic Genre: Modeling and Proposal for Didactic Intervention - Santos, Thais Cavalcanti dos [UNESP]; Canizares, Kathia Alexandra Lara [UNESP]; Manzoni, Rosa Maria [UNESP] (Univ Estadual Oeste Parana-unioeste, 2022)
Active teaching methodologies in teaching practice, often unconventional, are recurrent in the text of the National Common Curriculum Base (BNCC). In this context, working with fanzines at school can be a useful didactic proposal for planning activities that promote the development of skills and abilities, as well as language skills, in the textual production of students. Through the Sociodiscursive Interactionism (ISD) approach, working with the teaching of textual genres requires the realization of didactic transposition. Thus, in this work, from the area of Applied Linguistics, we present the theoretical-didactic modeling of the multimodal textual/discursive genre fanzine, aiming at recognizing the teachable dimensions of this genre. In the second stage, we report an experience on a fanzine production workshop, developed under the theoretical -methodological approach of the Teaching Guidance Activity (AOE). Likewise, we describe the steps that went through the planning, carrying out the experience and actions to produce the genre. This experience took place during an annual cultural event, at a public school in the interior of Sao Paulo, with students from the three grades of high school. We can say that the proposed didactic intervention, complementing the theories of ISD and AOE, using the fanzine textual genre, as a teaching and learning instrument is a possibility to be considered both in the planning of Portuguese Language teaching classes, as well as of school activities aimed at promoting different skills and
Keywords: Sociodiscursive Interactionism; Guiding Teaching Activity; Fanzine Multisemiotic Genre